Vegetation Analysis of Mount Sipiso-Piso Forest Area, Merek District, Karo Regency, North Sumatra - Ariasta Bereona Tarigan; Delvian Delvian; T Alief Aththorick (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2022)
Mount Sipiso-piso is an Old Volcanic Mountain and part of the Lake Toba Catchment Area (DTA). The location of the Forest on Mount Sipiso-piso is unique because the site of the Forest is at the top of Mount Sipiso-Piso. The area below the mountain is a dense Forest that stands in the peak area of Mount Sipiso-Piso has a role in maintaining water flows in the Mount Sipiso-Piso area, becoming a place for rainwater absorption, and maintaining ecosystem stability so that erosion or landslides do not occur in vulnerable areas. This study aimed to look at the diversity and evenness of Mount Sipiso-piso Forest vegetation types. Data analysis techniques include Important Value Index (INP), Diversity Index (H'), and Evenness Index (E). The results showed that 20 families and 23 plant species from 1539 individuals were found in the field. The Important Value Index (INP) indicates that different individuals dominate the forest community at each level. The index of the diversity of Mount Sipiso-Piso Forest vegetation is categorized as moderate in the saplings, poles, and trees class and the low category in the undergrowth, woody shrubs, and seedlings class. For the species evenness index, the category is expected in the undergrowth and seedling class, the medium type is in the woody shrub and tree class, and the high sort is in the sapling and pole class.Keywords: Sipiso-Piso Mountain, Forest, Vegetation, Diversity, Evenness.